COMMODIFICATION OF RELIGION-BASED AUDIOVISUAL CONTENT ON THE YOUTUBE CHANNEL (CASE STUDY ON ISLAM POPULER YOUTUBE CHANNEL) - Khairul Syafuddin; Tangguh Okta Wibowo (Lafadz Jaya Publisher, 2023)
Technological developments have made it easier for people to consume and produce audiovisual content on social media, including through the use of the Islam Populeric YouTube channel which provides diverse information for its users. The channel owners monetize their content, making their content production practices profit-oriented. This article analyzes how Islam Populer commodifies Islamic-themed content to generate profits, as well as the exploitation of new media workers. The article shows that Islam Populer successfully commodifies the values and teachings of Islam in their content, generating profits for their media endeavors. However, Islam Populer remains a commodity for YouTube, as the account's performance attracts advertisers who benefit YouTube the most. This makes Islam Populer one of the parties that are exploited in the context of media work.